THE CORRELATION BETWEEN FREQUENCY OF WATCHING ENGLISH MOVIES AND VOCABULARY MASTERY - Saiful Saiful; Hamid Ismail Abdullah; Rina Asrini Bakri (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine whether there is a correlation between frequency of watching English movies and vocabulary mastery of SMAN 1 Bontonompo Selatan Gowa Regency. This study uses the descriptive method. The population of this research was the second grade of SMAN 1 Bontonompo Selatan Gowa Regency. The sample is 20 students by using purposive sampling in one class. In collecting the data, researchers used a questionnaire instrument to look at the frequency of students’ watching movie and vocabulary tests. The results of this study indicated that there is a significant relationship between the level of frequency of watching movies in English and the students' vocabulary mastery. It can be proved through the data and test the value of r-table where the value of r-test (0.358) is lower than r-table (0.444). The researchers concluded that there is a low correlation to the frequency of watching movies in English and the students' vocabulary mastery.